Non Performing Financing di Masa Pandemi Covid-19 dan Strategi Menghadapinya - Lailatul Hasanah; Safwira Guna Putra (Jurnal Perbankan Syariah, 2022)
This research aims to answer how the impact of the COVID-19 pandemic on non-performing financing at PT BPRS Dinar Ashri Mataram and what are the strategies for dealing with and mitigating the financing risks. The analysis uses a descriptive qualitative approach. The primary data collected by direct observation and conducting semi-structured interviews with several employees by considering the position and job role of the employee. The results showed that at the beginning pandemic, NPF ratio increased from 0.65% in 2019 to 0.77% in 2020. However, in 2021 the NPF ratio decreased to 0.70%. This NPF ratio is still safe compared to the average national NPF ratio, this is due to the success of PT. BPRS Dinar Ashri implementing the right mitigation strategy which is, among others, awarenes to do restructuring financing facility which is experiencing a decline business conditions.